How SARS-CoV-2 and Comparable Pathogens Can Be Defeated in a Single Day: Description and Mathematical Model of the Carrier Separation Plan (CSP) - Epstein, Robert; Houser, Connan; Wang, Ruixiao (Frontiers in Public Health, 2021)
A simple, common-sense, three-component procedure—the Carrier Separation Plan (CSP)—can immediately halt the transmission of SARS-CoV-2 or a comparable pathogen, allow the safe reopening of an entire economy without the need for social distancing, and quickly eradicate the pathogen from the population (assuming the pathogen can be killed by the immune systems of the carriers). The three components are (a) nearly simultaneous self-testing for the pathogen by an entire population, followed rapidly by (b) nearly simultaneous self-isolation of carriers, and (c) secondary screening at entrances to facilities where people congregate. After a period of preparation lasting roughly 5–10 weeks, these steps could and probably should be taken in a single day. The power of this methodology has already been demonstrated in varying degrees with groups ranging in size from 1,000 to 11 million. Although this plan might seem daunting, its costs are minimal compared to the losses we have incurred by relying on half measures, and the US and other countries have the technological, logistical, and industrial capacities to implement this plan in a matter of weeks. With proper messaging during the weeks leading up to the testing, compliance in such a program is likely to be high given the potential benefits, and because participation is voluntary and testing is noninvasive, the legal and ethical issues associated with such a program are minimal – trivial, in fact, compared to those associated with imposing a months-long lockdown on an entire population. A SIRD/CSP model suggests that the single-day testing and separation procedure will substantially lower the number of infections, even if compliance with the procedure is modest. Modeling also suggests that when long-term secondary screening is added to the 1-day procedure, over time, the pathogen is eradicated from the population. This can occur even when compliance with secondary screening is itself relatively low.